Strategi Pembangunan Pertanian Berkelanjutan di Pedesaan Berbasis Citra Drone (Studi Kasus Desa Sukadamai Kabupaten Bogor) - ihsan arham; Sofyan Sjaf; Dudung Darusman (Jurnal Ilmu Lingkungan, 2019)
Most of the agricultural sector activities are in rural area. Rural and agricultural development requires accurate spatial information so that accuracy in sustainable development planning can be attained. This study was aimed to determine the strategy of sustainable agriculture development planning in a rural area. This research method used a spatial data approach acquiring village imagery produced using a drone. The actual land use analysis used ArcGIS software through a participatory digitization process. Analysis of land carrying capacity using the approach of land availability and land requirements. The results of the analysis became a reference for compiling the direction of planning for sustainable agricultural village development. Analysis of alternative program priorities using the Analytical Hierarchy Process (AHP) approach. The study found that agricultural areas dominated land use in Sukadamai Village with an area of 112,942 ha (42,693%). Land carrying capacity in Sukadamai Village was in a deficit with a comparison ratio of land availability (SL) to land requirements (DL) of 0.22. The strategy of sustainable agricultural development that can be done is the innovative application of effective and efficient land intensification. The program prioritized the criteria of social justice and maximized the government's role in realizing development goals.